PENGARUH MAKROEKONOMI DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN BANK DIGITAL SELAMA PANDEMI COVID-19 - Utami, Aulia Putri; Hascayani, Tyas Danarti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The increase in stock prices is considered to be an indicator of increasing firm value. During the pandemic, there was a contradiction between stock price movements and the fundamental conditions of digital banking companies. This research was conducted to determine the effect of macroeconomics as reflected by gross domestic product (GDP), interest rates (R), exchange rates (NT), inflation (INF), and the effect of financial performance as reflected by return on assets (ROA) and loan to deposit ratio (LDR) to firm value (MBV) of digital banks during the Covid-19 pandemic. 48 samples from 6 companies with 8 time periods moving quarterly from 2020-2021 were analyzed using multiple linear regression panel data with the selected common effect model (CEM). The results of this study are PDB and R have a positive and significant effect on MBV, while NT, INF, LDR have a negative and significant effect on MBV. And only ROA has a positive and insignificant effect on MBV. However, simultaneously all the dependent variabels have a significant effect on MBV.